The Importance of Health Insurance Reform - Kassebaum, Nancy (Maine Policy Review, 1995)
In her commentary, Republican Senator Nancy Kassebaum of Kansas outlines a proposed bipartisan health insurance reform act which she will introduce in the Senate next year.
Keywords: healthcare reform; health insurance reform